Carbon Reserves in The Forest Stand In The Maninjau Natural Reserve Area, Silayang-Malabur Rehabilitation Block, Agam District - Lubis, Novia Sherina A.; Putri, Irma Leilani Eka (Journal of Climate Change Society, 2023)
The Maninjau Nature Reserve is a conservation forest area located in Agam Regency and Padang Pariaman Regency. Based on its management, the Maninjau Nature Reserve is divided into protection blocks, rehabilitation blocks and special blocks. Meanwhile, Silayang-Malabur is included in the rehabilitation block where this block has suffered damage caused by illegal logging and conversion of forests into fields which have an impact on reducing carbon stocks. Therefore, it is necessary to conduct this research to determine stored carbon stocks. This research was conducted in the Maninjau Nature Reserve area, Silayang-Malabur Rehabilitation Block, Agam Regency, which was carried out from December 2022 - January 2023. This type of research was descriptive research by collecting data on plants in forest stands. Data collection used purposive random sampling which was divided into 2 research areas, namely natural forest and disturbed natural forest. The sample plots used were a single plot of 3 randomly distributed plots in each study area. Based on the results of research on carbon stocks in forest stands in the Maninjau Nature Reserve area of ​​Silayang-Malabur Rehabilitation Block, Agam Regency of 182,812 tons C/ha where carbon stocks in natural forest areas are 148,415 tons C/ha while carbon stocks in disturbed natural forest areas are 34,397 tons C/ha. According to the Ministry of Forestry's Bappenas criteria, it was concluded that the total carbon stock in the Maninjau CA area is in the high category.